Economic Policy in Crisis: An Analysis of Disaster Management and Asset Centralization According to Genesis 47 - Sukanto Limbong; Daniel Panjaitan (Journal of Economics and Social Sciences (JESS), 2026)
Food crises frequently serve as catalysts for massive structural transformations within a state's political economy. This article analyzes the famine-relief policies in Genesis 47:13–26, focusing on the duality between disaster management and asset centralization by the Egyptian throne through Joseph's bureaucracy. Utilizing a biblical political economy framework and socio-historical analysis, this study examines how famine mitigation shifted from an emergency relief scheme into a systematic instrument of land nationalization and the subjugation of the peasantry.The findings reveal that while Joseph’s state-led disaster management successfully preserved human life, it demanded an exorbitant structural price: the eradication of private landownership and the transformation of free citizens into state-dependent serfs. This centralization of assets created a precedent of fiscal imperialism that reinforced Pharaonic absolutism. The article concludes that the narrative of Genesis 47 does not merely record a logistical success, but functions as a sharp theological and ethical critique against exploiting crises for the accumulation of institutional power. This study offers a vital contribution to contemporary economic ethics regarding agrarian justice in emergency contexts.